Facilitators, barriers and service availability for delivering integrated care for the triple elimination of HIV, syphilis and hepatitis B vertical transmission in Uganda: a multi-site explanatory mixed methods study - Andrew Kazibwe; Emmanuel Olal; Andrew Mijumbi Ojok; John Vianney Kigongo; Henry Kafumbe; Maria Prima Niwampeire; Charity Gloria Toskin; Doreen Ondo; Linda Kisaakye Nabitaka; Patience Mwine; David Kagimu; Anna Lawino; et al. (BMC Health Services Research)
Abstract Background Elimination of vertical transmission of HIV, syphilis and hepatitis B is part of the global aspiration to end the three infections as public health threats by 2030. Whereas global and national policy guidelines recommend integration of screening, prevention and treatment for the three infections in maternal and child health (MCH) service delivery points, progress has been slow. We aimed to explore the health system factors that facilitate and hinder optimal integration of triple elimination services within the MCH platforms. Methods This was a cross-sectional, explanatory mixed methods multi-site study implemented in two regions of Uganda, conducted in July – August 2024. Firstly, we used an observation checklist to assess for the availability of services and commodities required for provision of triple elimination care at 20 health facilities (two regional referral hospitals, two general hospitals, two specialized outpatient TASO clinics, five HCIVs, eight HCIIIs and one HCII), and computed a percentage service and commodity availability score for each site, and average for the sites. We then used findings from this assessment to guide open-ended probing during key informant interviews and focus group discussions among ten key informants and 43 focus group discussion participants. Interviews and discussions were recorded, transcribed verbatim, and then analysed manually. We categorized responses as either facilitators or barriers and extracted quotes, by theme, based on the World Health Organization’s health systems building blocks framework. Results The average percentage score of service and commodity availability was 61.8% (range: 46.4–78.6%) in Acholi region and 66.1% (range: 53.6–78.6%) in Teso region. We found that presence of trained focal persons, district accountability fora, routine data collection and utilization, and availability of motivated community health workers facilitated triple elimination service integration. Key barriers included limited district health team engagement, frequent stock-outs of diagnostic and treatment commodities, health personnel shortages and high reporting burden. Conclusions Health facility service readiness and availability percentage scores differed across facilities and between the two regions. Several health system factors facilitate integrated service provision for elimination of HIV, syphilis and hepatitis B vertical transmission. This integration is, however, constrained by a number of health system barriers. Further implementation research could contribute to addressing the various health system constraints and adoption of strategies for service integration tailored to site contexts.